ECLIPSING BINARY STARS : LIGHT CURVE MODELS AND SOFTWARE - Niarchos, P. G. (Одеські астрономічні публікації, 2017)
The importance of studying Eclipsing Binary Stars for the determination of fundamental stellar data is sketched. The eclipsing binaries, originally classified phenomenologically, are now understood on the basis of much firmer physics and the improved understanding has led to a morphological basis of classification. The main light curve models developed since Russell’s era are presented along with the respective programs for analysis (Kallrath & Milone 1999). These models are based on the geometric effects due to eclipses and on physical proximity effects between the components. Significant progress was made in the early 1970s, when models and programs were developed to compute (synthetic) light and velocity curves directly. Such models and programs were based on spherical stars, ellipsoidal geometry and on Roche geometry. During the last 25 years the analysis of photometric and spectroscopic data of eclipsing binaries has been performed by means of synthetic light curve programs based on Roche geometry. The synthetic light curve programs, based on physical models, have contributed to our understanding of physical processes in stars and have been used to solve several important astrophysical problems. A desirable feature of a light curve program is the ability to incorporate additional astrophysics. There is a continuing need to improve the model physics, as we become more aware of the observational properties of stars.